(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This comprehensive article provides an insightful exploration into the intricate world of linguistics, focusing on the fundamental aspect of morphology—the study of word structure and formation. The author adeptly navigates through the diverse classifications of words based on their internal components, shedding light on the intricate relationships between morphemes and their roles in shaping language. The article begins by elucidating the foundational elements of word structure, emphasizing root words as the core components carrying primary meanings. It adeptly delves into the nuanced classifications of affixes—prefixes, suffixes, and even infixes—illustrating how these morphemes modify or alter the meanings and grammatical functions of root words. Further, the piece elucidates the distinction between derivational and inflectional morphemes, highlighting their roles in creating new words or indicating grammatical nuances without changing fundamental meanings. The exploration extends to compound words, clitics, and zero derivation, offering a comprehensive view of how languages combine, adapt, and create meaning through morphological processes.